Cherenkov radiation from the target with predetermined dielectric properties, produced by a 3D-printer; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 402 - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Bleko V. V. Vitold Vladislavovich; Soboleva V. V. Veronika Vyacheslavovna; Stuchebrov S. G. Sergey Gennadevich (2017, 2017)
Title screen